The challenges faced by SMES entrepreneurs: a case study at Melaka Tengah / Amirah Che Abdul Halim and Nor Suhada Anuar - Che Abdul Halim, Amirah; Anuar, Nor Suhada (Faculty of Administrative Science and Policy Studies, 2012)
The study seeks to determine the challenges faced by SMEs Entrepreneurs. A sample of 92 of 120 SMEs Entrepreneurs at Melaka Tengah had been selected for this study. The findings showed that the independent variables or factors that support our hypothesis are financial, technology, managerial competencies and human resources. It means that all these four factors determine their relationship with the challenges faced by SMEs Entrepreneurs. Simple random sampling will be used to distribute the questionnaire to selected respondents. Based on this finding,managerial competency is the most contributors to the challenges faced by SMEs Entrepreneurs. While, all those four independent variables have a significant relationship with the challenges faced by SMEs Entrepreneurs. This is due to the result of correlation coefficient that has been used. In conclusion, financial, technology, managerial competencies and human resources contribute to the challenges faced by SMEs Entrepreneurs.